Composite Resin Bond Strength to Zirconia and Base Metal Alloys Using Two Types of Intraoral Porcelain Repair Systems - Mahnaz Arshad; Rasamedin Gordan; Paniz Farrokhi; Sareh Habibzadeh (Frontiers in Dentistry, 2023)
Objectives: This study aimed to evaluate the shear bond strength (SBS) of two repair composites (Crea.lign vs. PermaFlo) to a base metal alloy and zirconia ceramic.